(untitled) (Journal of Medical & Health Sciences Review, 2025)
Cardiovascular diseases are a major global issue, demanding accurate and timely diagnosis for effective intervention. Integrating advanced imaging techniques, such as computed tomography, coronary angiography (CTCA), and coronary artery calcium (CAC) Scores, has notably improved diagnostic precision and risk assessment. This research was conducted to find the association between coronary calcium score and stenosis percentage in coronary arteries, which is diagnosed by CT angiography in patients over 40 years old and with moderate symptoms of coronary artery disease. Data was collected from the Radiology Department of the Rawalpindi Institute of Cardiology, Rawalpindi. Eligible patients who met the inclusion criteria were identified, and relevant data was collected. The prevalence of coronary artery disease (CAD) was highest in the 61-70 age group (33%). Male participants exhibited a higher CAD prevalence (55%) than females (45%). Hypertension was present in 66% of patients, 42% had a history of CAD in the family, Smoking was seen in 33%, and diabetes in 31%. The p-value representing the association between coronary calcium score categories and the Stenosis percentage diagnosed by CTCA is 0.01. This study concluded a significant positive correlation between coronary calcium score and Stenosis percentage in coronary arteries diagnosed by CT angiography.